(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
Uyghur manuscripts were written mainly after the dissolution of the Orkhan Uyghur Khanate in the 9th century. In the second half of the century, the new place of residence of the Uyghur tribes, who formed an independent state, was found in the Turfan region. Medical orders are among them. Most of the medical writings of the Uyghurs are written in Uyghur characters, which evolved from the Sogdian alphabet and became systematic over time, becoming the common alphabet not only of the Uyghurs, but also of Turkic communities of various cultural backgrounds. There are also texts with Brahmi characters (Gabain 1954) and Syriac characters (R. Lmez, 1996). The exact dates of the texts are not given in the sources, but the fact that they appeared as a result of research conducted in Eastern Turkestan indicates that they belong to the period of the Kocho Uighur state, which was established in this region. In addition, the word atachi bakshi mentioned in the texts (Dec 1932:8) indicates that among the Uighurs there are Buddhist monks who perform medical duties or that medical services are also provided in Buddhist institutions (Bayat 2010: 255). Based on this information, it can be said that the Uighur medical texts belong to a relatively late period.